2016 IMS Recommendations on women's midlife health and menopause hormone therapy. (3rd March 2016) - Baber, R. J.; Panay, N.; Fenton, A.
Abstract: The International Menopause Society (IMS) has produced these new 2016 recommendations on women's midlife health and menopause hormone therapy (MHT) to help guide health-care professionals in optimizing their management of women in the menopause transition and beyond. The term MHT has been used to cover therapies including estrogens, progestogens and combined regimens. For the first time, the 2016 IMS recommendations now include grades of recommendations, levels of evidence and 'good practice points', in addition to section-specific references. Where possible, the recommendations are based on and linked to the evidence that supports them, unless good-quality evidence is absent. Particular attention has been paid to published evidence from 2013 onwards, the last time the IMS recommendations were updated. Databases have been extensively searched for relevant publications using key terms specific to each specialist area within menopause physiology and medicine. Information has also been drawn from international consensus statements published by bodies such as the IMS, the European Menopause and Andropause Society and the North American Menopause Society. The recommendations have been produced by experts derived mainly from the IMS, with the assistance of key collaborators where deemed advantageous. In preparing these international recommendations, experts have taken into account geographical variations in medical care, prevalence of diseases, and country-specific attitudes of the public, medical community and health authorities towards menopause management. The variation in availability and licensing of MHT and other products has also been considered.